Disruptive Behaviors and Intellectual Disability: Creating a New Script - Chan, Melvin Chin-Hao; Campbell, Mackenzie; Beyzaei, Nadia; Stockler, Sylvia; Ipsiroglu, Osman S. (Frontiers in Psychiatry, 2022)
Background: Terms currently used to describe the so-called challenging and disruptive behaviors (CBDs) of children with intellectual disabilities (ID) have different connotations depending on guiding contextual frameworks, such as academic and cultural settings in which they are used. A non-judgmental approach, which does not attempt to establish existing categorical diagnoses, but which describes in a neutral way, is missing in the literature. Therefore, we tried to describe CDBs in youth with ID in an explorative study. Methods: Interviews with families investigated the CDBs of five youth with Down syndrome. At home, families tracked youth’s sleep/wake behaviors and physical activity. Youth were observed in a summer school classroom. The collected information and suggested explanatory models for observed CDBs were reviewed with the families. Results: We grouped CDBs as challenging, if they were considered to be reactive or triggered, or unspecified, if no such explanatory model was available. A third category was created for light-hearted CDBs: goofy, acknowledging the right to laugh together with peers. We found some relationships between sleep, physical activity, and CDBs and developed an explorative approach, supporting a child-centered perspective on CDBs. Conclusion: The controversial discussions on terminology and management of CDBs in the literature demonstrate the need for a non-judgmental approach. Such an explorative approach, allowing non-professionals to not label, has been missing. The fact that, up to now, the light-hearted behaviors of an individual with ID have not been integrated in commonly-used behavioral checklists as their natural right, proves our concept and indicates that a paradigm change from judgment-based to exploratory-driven approaches is needed.